Smart Glasses with Augmented Reality Workflow; A Modern Tool for Triage in Mass Casualty Incidents - Korakot Apiratwarakul; Lap Woon Cheung; Chatkhane Pearkao; Kamonwon Ienghong (Archives of Academic Emergency Medicine)
Introduction: Smart glasses with an augmented reality workflow have emerged as a new tool for triage in mass casualty incidents (MCIs). This study aimed to investigate the accuracy and time efficiency of smart glasses in MCIs triage.